Seed Production Affects Maternal Growth and Senescence in Arabidopsis - Wuest, Samuel Elias (Plant Physiol, 2016)
Correlative control (influence of one organ over another organ) of seeds over maternal growth is one of the most obvious phenotypic expressions of the trade-off between growth and reproduction. However, the underlying molecular mechanisms are largely unknown. Here, we characterize the physiological and molecular effects of correlative inhibition by seeds on Arabidopsis (Arabidopsis thaliana) inflorescences, i.e. global proliferative arrest (GPA) during which all maternal growth ceases upon the production of a given number of seeds. We observed transcriptional responses to growth- and branching-inhibitory hormones, and low mitotic activity in meristems upon GPA, but found that meristems retain their identity and proliferative potential. In shoot tissues, we detected the induction of stress- and senescence-related gene expression upon fruit production and GPA, and a drop in chlorophyll levels, suggestive of altered source-sink relationships between vegetative shoot and reproductive tissues. Levels of shoot reactive oxygen species, however, strongly decreased upon GPA, a phenomenon that is associated with bud dormancy in some perennials. Indeed, gene expression changes in arrested apical inflorescences after fruit removal resembled changes observed in axillary buds following release from apical dominance. This suggests that GPA represents a form of bud dormancy, and that dominance is gradually transferred from growing inflorescences to maturing seeds, allowing offspring control over maternal resources, simultaneously restricting offspring number. This would provide a mechanistic explanation for the constraint between offspring quality and quantity.